Glutamate Acts as a Neurotransmitter for Gastrin Releasing Peptide-Sensitive and Insensitive Itch-Related Synaptic Transmission in Mammalian Spinal Cord. Issue 1 (24th June 2011) - Koga, Kohei; Chen, Tao; Li, Xiang-Yao; Descalzi, Giannina; Ling, Jennifer; Gu, Jianguo; Zhuo, Min
Itch sensation is one of the major sensory experiences of human and animals. Recent studies have proposed that gastrin releasing peptide (GRP) is a key neurotransmitter for itch in spinal cord. However, no direct evidence is available to indicate that GRP actually mediate responses between primary afferent fibers and dorsal horn neurons. Here we performed integrative neurobiological experiments to test this question. We found that a small population of rat dorsal horn neurons responded to GRP application with increases in calcium signaling. Whole-cell patch-clamp recordings revealed that a part of superficial dorsal horn neurons responded to GRP application with the increase of action potential firing in adult rats and mice, and these dorsal horn neurons received exclusively primary afferent C-fiber inputs. On the other hands, few Aδ inputs receiving cells were found to be GRP positive. Finally, we found that evoked sensory responses between primary afferent C fibers and GRP positive superficial dorsal horn neurons are mediated by glutamate but not GRP. CNQX, a blocker of AMPA and kainate (KA) receptors, completely inhibited evoked EPSCs, including in those Fos-GFP positive dorsal horn cells activated by itching. Our findings provide the direct evidence that glutamate is the principal excitatory transmitter between C fibers and GRP positive dorsal horn neurons. Our results will help to understand the neuronal mechanism of itch and aid future treatment for patients with pruritic disease.